Discrete-time feedback stabilization for hybrid neutral stochastic systems - Bai, L.; Li, Q.; Xu, Honglei; Zhang, Q.; Zhang, Y. (World Scientific, 2017)
© 2018 World Scientific Publishing Company In this paper, we study the exponential stabilization problem in (Formula presented.)th moment of hybrid neutral stochastic systems by discrete-time feedback controls. By extending Mao’s method, we first derive an upper bound of state observation duration of the corresponding systems with continuous-time state observation feedback controls. We further establish exponential stabilization conditions in (Formula presented.)th moment for the hybrid neutral stochastic system. The obtained results have potential applications to stabilize practical hybrid systems with interconnected stochastic oscillators.